THE CURRENT STATE AND THE PERSPECTIVES OF FRUIT-GROWING ENTREPRENEURSHIP IN THE NORTHERN DEVELOPMENT REGION OF THE REPUBLIC OF MOLDOVA - GRINCIUC, Liliana (Economy and Sociology, 2021)
Currently, the role and importance of SMEs in the development of the national economy are characterized by such features as: the direct contribution to the formation of the GDP in every country is, as a rule, between 55-95%; new jobs creation; boosting competition; increasing exports; innovations and technologies fostering. The effectiveness of entrepreneurial activity in fruit growing is characterized by the application of new fruit production technologies, such as intensive and super intensive system. The purpose of the research was to analyze fruit growing entrepreneurship in the Northern Development Region of the Republic of Moldova based on the data of „Domultera” LLC in Floresti district. The objective of the research was to analyze fruit-growing entrepreneurship in the Northern Development Region of the Republic of Moldova by describing the realities and perspectives in the field. It has been found out that applying super intensive and intensive technology to fruit growing is efficient. This fact can be explained by the reduction in production costs and the increase in global fruit production, sales revenue from the obtained production and gain profit, which have influenced the increased profitability level of up to 127.76% in 2017 and 86.15% in 2018 in the case of apple cultivation by applying the super intensive system. Apples and plums cultivation by applying intensive technology also increases the economic efficiency when trees begin to bear fruits.